Crosstalk between Heme Oxygenase-1 and Iron Metabolism in Macrophages: Implications for the Modulation of Inflammation and Immunity - Joseana de Oliveira; Marina B. Denadai; Diego L. Costa (MDPI AG, 2022)
Heme oxygenase-1 (HO-1) is an enzyme that catalyzes the degradation of heme, releasing equimolar amounts of carbon monoxide (CO), biliverdin (BV), and iron. The anti-inflammatory and antioxidant properties of HO-1 activity are conferred in part by the release of CO and BV and are extensively characterized. However, iron constitutes an important product of HO-1 activity involved in the regulation of several cellular biological processes. The macrophage-mediated recycling of heme molecules, in particular those contained in hemoglobin, constitutes the major mechanism through which living organisms acquire iron. This process is finely regulated by the activities of HO-1 and of the iron exporter protein ferroportin. The expression of both proteins can be induced or suppressed in response to pro- and anti-inflammatory stimuli in macrophages from different tissues, which alters the intracellular iron concentrations of these cells. As we discuss in this review article, changes in intracellular iron levels play important roles in the regulation of cellular oxidation reactions as well as in the transcriptional and translational regulation of the expression of proteins related to inflammation and immune responses, and therefore, iron metabolism represents a potential target for the development of novel therapeutic strategies focused on the modulation of immunity and inflammation.